Prevalência de transtorno do humor bipolar em uma amostra de idosos atendidos no programa saúde da família do município de Porto Alegre - Porciúncula, Letícia Rodrigues (2015)
In recent years, there have been significant changes in the socioeconomic and health conditions of the population and hence the demographic structure, resulting in a significant growth of the elderly population and causing an increased risk of acquiring neurological and psychiatric diseases. Among the psychiatric illness, bipolar disorder is responsible for a significant portion of the functional impairment around the world. However, international data show that affective disorders have a prevalence of approximately 11.3% of the population, or up to 25% of the elderly. Furthermore, it is one of the diseases that generates and social losses in family relationships, which can lead to suicide in approximately 15% of patients. The aim of this study was to evaluate the prevalence of Bipolar Affective Disorder (BD) in a random sample of elderly attended by the Family Health Strategy (Estratégia Saúde da Família, ESF) in Porto Alegre. The study is cross-sectional with prospective data collection. The sample consisted of 550 randomly selected elderly 30 Family Health Teams in the Municipality of Porto Alegre (ESF / POA) randomized stratified mode for district. For diagnoses, psychiatrists with experience in assessment of older adults used the diagnostic criteria of DSM-5. Regarding the results: a total of 5.8% (n = 32) of the sample subjects presented the Bipolar Affective Disorder, 59.4% (n = 19) diagnosed with type I and 40.6% (n = 13 ) type II. Of this total, 1.5% (n = 8) have current frame TAB and 4.4% (n = 24) TAB board in the past. Among seniors who had the disorder, some significant associations can be highlighted: with suicide attempt in life (21.6%; p = 0.001) with the risk of suicide (15.7%; p = 0.001) and an association borderline between the elderly having a partner with TAB (8.3%; p = 0.053). Variables associated with THB are female, having a partner and suicide risk. In this study, there has been a significant prevalence of the disorder in the elderly and it was possible to identify predictors through analyzes.The findings of this study are worrisome, if need be replicated in other locations and samples.